ANTIFUNGAL STUDY OF UNCARIA GAMBIR ROXB. (UGR) EXTRACT AGAINST GANODERMA SP. IN VITRO: STUDI ANTIFUNGI EKSTRAK UNCARIA GAMBIR ROXB. (UGR) TERHADAP GANODERMA SP. SECARA IN VITRO - Nugroho, Rylo; Iskandar, Dodi; Rista Delyani; Danie Indra Yama; Muliani (ROCE : Jurnal Pertanian Terapan, 2025)
Ganoderma sp. is a pathogenic fungus that causes basal stem rot in oil palms, leading to significant yield losses. This study explores the antifungal potential of Uncaria gambir Roxb. extract against Ganoderma sp. using in silico and in vitro methods. In silico analysis from the KNApSAcK and PASS Online databases identified 18 secondary metabolites with probability activity (Pa) values ranging from 0.5 to 0.7, indicating high potential. Cinchonain Ia, an alkaloid with the highest Pa value of 0.638, has poor solubility. In vitro tests on U. gambir extract at various concentrations (0%, 1.5%, 2%, 2.5%, and 3%) showed that the extract was ineffective in inhibiting the growth of Ganoderma sp. Further research with variations in solvents, extraction methods, and formulations is needed to optimize the antifungal activity of this extract.